2022
DOI: 10.1590/1414-431x2021e11504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alzheimer’s disease of varying severity on cardiac and autonomic function

Abstract: Alzheimer's disease (AD) is one of the most common neurodegenerative diseases in the elderly. The aim of this study was to explore the effects of AD on cardiac function and autonomic nervous function, and the feasibility of electrocardiogram (ECG) in monitoring the development of AD. APP/PS1 double transgenic mice were used in the Morris water maze (MWM) experiment to evaluate the changes of cognitive ability of AD mice, then the non-invasive ECG acquisition system was used and the changes of ECG intervals and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Only one human study has explored HRV during sleep in patients with MCI and found that parasympathetic regulation during NREM sleep, but not during wakefulness or REM sleep, was impaired in patients with MCI compared with healthy controls 76 . In animal studies, only one study explored the changes of autonomic function during wakefulness with short-term HRV recordings during AD progression and found that APP/PS1 mice had no significant changes in autonomic function at 5 months of age but had significantly higher sympathetic function and lower parasympathetic function after 7 months of age when compared with their age-matched WT mice 77 . However, no relevant findings about autonomic function during sleep have been reported in animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Only one human study has explored HRV during sleep in patients with MCI and found that parasympathetic regulation during NREM sleep, but not during wakefulness or REM sleep, was impaired in patients with MCI compared with healthy controls 76 . In animal studies, only one study explored the changes of autonomic function during wakefulness with short-term HRV recordings during AD progression and found that APP/PS1 mice had no significant changes in autonomic function at 5 months of age but had significantly higher sympathetic function and lower parasympathetic function after 7 months of age when compared with their age-matched WT mice 77 . However, no relevant findings about autonomic function during sleep have been reported in animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…PSNS input increases cerebral perfusion, whereas SNS input reduces cerebral perfusion during sleep [7]. The PSNS serves as a "brake" for the SNS [8][9][10]. The decline in PSNS activity accelerates with age, particularly in individuals with AD, which gradually results in ANS dysregulation [9,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The PSNS serves as a "brake" for the SNS [8][9][10]. The decline in PSNS activity accelerates with age, particularly in individuals with AD, which gradually results in ANS dysregulation [9,[11][12][13]. Discoordination of SNS and PSNS activities in individuals with AD resulting in ANS dysregulation appears to be associated with unstable and irregular circadian rhythms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations